Influence of temperature and prey type on life-table parameters and consumption rate of Stethorus gilvifrons (Mulsant) (Coleoptera: Coccinellidae) on three tetranychid mites - Ashraf Said Elhalawany; Ahmad I. Amer; Enas M. Kassem (Persian Journal of Acarology)
The two-spotted spider mite Tetranychus urticae Koch, the date palm dust mite Oligonychus afrasiaticus (McGregor), and the citrus brown mite Eutetranychus orientalis (Klein) of family Tetranychidae are key pests of fruit trees, field crops, and ornamentals that cause significant yield losses. The purpose of this research was to assess the effect of three constant temperatures (22, 27, and 32 °C) on the developmental time, life-table parameters, and consumption rate of the predatory beetle Stethorus gilvifrons (Mulsant) on maize leaf disks with T. urticae, O. afrasiaticus, and E. orientalis as food. The results indicated a significant difference between the three different temperatures and prey types. The shortest developmental time was recorded on T. urticae (9.30 and 10.10 days) at 32 °C, while the longest was on E. orientalis (23.34 and 22.50) at 22 °C for females and males, respectively. The shortest female longevity was on E. orientalis (21.14 days) at 32 °C, and the longest was 39.12 days on T. urticae at 22 °C. The fecundity increased as temperature increased, from 114.6 eggs with a daily rate of 3.81 eggs per female/day at 22 °C to 235.0 eggs with a daily rate of 10.78 eggs per female/day at 32 °C on T. urticae. The highest net reproductive rate (R0), intrinsic rate of natural increase (rm), and finite rate of increase (λ) were recorded at 32 °C, whereas the lowest values were recorded at 22 °C when predatory beetles S. gilvifrons were fed on three prey diets. Gross reproduction rate (GRR) recorded the highest value (132.8 offspring/individual) when fed on T. urticae at 32 °C and the lowest value (55.30 offspring/ individual) when fed on E. orientalis at 22 °C. The highest consumption rate of adult males and females was 226.8 and 245.4 individuals when fed on O. afrasiaticus at 22 °C, while the lowest was 123.6 and 133.8 individuals on E. orientalis at 32 °C. Thus, the results obtained here revealed that temperature and prey diets influence the developmental rate and reproduction of S. gilvifrons. Additionally, T. urticae is better for mass rearing of S. gilvifrons than O. afrasiaticus and E. orientalis as food.